Circadian, hormonal, and sleep rhythms: effects on cancer progression implications for treatment - Jagielo, Annemarie D.; Benedict, Catherine; Spiegel, David (Frontiers in Oncology, 2023)
Circadian, hormonal, and sleep rhythm disruptions are commonly experienced concerns among cancer patients throughout the cancer care continuum. This review aims to summarize the existing literature on circadian, hormonal, and sleep rhythms in the oncological population, focusing on circadian disruption and physiological and psychological abnormalities, disease progression, and chronomodulated treatment approaches. The findings demonstrate that subjectively and objectively measured circadian rhythm disruption is associated with adverse mental health and disease outcomes in patients with cancer. Chronomodulated chemotherapy, light therapy, cognitive behavioral therapy for insomnia, and physical activity have shown evidence of effectiveness in improving sleep, and occasionally, disease outcomes.